2022
DOI: 10.31004/cendekia.v6i2.1405
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review: Kemampuan Pemahaman Matematis Siswa dalam Menyelesaikan Masalah Matematika

Abstract: Penelitian ini bertujuan untuk melakukan kajian literatur terkait dengan kemampuan pemahaman konsep matematis siswa dalam mengerjakan soal matematika pada jenjang SD, SMP, SMA, dan Perguruan Tinggi. Metode yang digunakan dalam penelitian adalah Systematic Literature Review (SLR), yang terdiri dari 53 sampel hasil penelitian kemampuan pemahaman konsep matematis siswa. Sampel terdiri dari jurnal terindeks yang diterbitkan pada periode 2015 – 2022. Pengumpulan data dilakukan dengan mendokumentasikan semua artikel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
2
1
0
5
Order By: Relevance
“…On the other hand, the study on students' mathematical literacy based on: learning style and cognitive style conducted in Sumatera and Kalimantan is considering low because it was a thirteenth of the research conducted in Java. This is in line with the statement the research about students' mathematics ability was mostly conducted in Java while its research in Papua is still in a low number (Ariati & Juandi, 2022;Khairunnisa et al, 2022). Aswin & Juandi (2022) also found similar result which stated the research about students' error was largely conducted in Java.…”
Section: Study By Research Locationsupporting
confidence: 84%
“…On the other hand, the study on students' mathematical literacy based on: learning style and cognitive style conducted in Sumatera and Kalimantan is considering low because it was a thirteenth of the research conducted in Java. This is in line with the statement the research about students' mathematics ability was mostly conducted in Java while its research in Papua is still in a low number (Ariati & Juandi, 2022;Khairunnisa et al, 2022). Aswin & Juandi (2022) also found similar result which stated the research about students' error was largely conducted in Java.…”
Section: Study By Research Locationsupporting
confidence: 84%
“…The research in Java took 11 from 17 samples in this study, this was also found by other researchers about students' mathematics ability was mostly conducted in Java (Khairunnisa et al, 2022;Ariati & Juandi, 2022). This could be because most of Indonesia's population is in Java.…”
Section: Study By Research Locationsupporting
confidence: 76%
“…Metode penelitian ini dilakukan dengan mengidentifikasi, mengkaji, mengevaluasi serta menafsirkan semua penelitian yang diperoleh. Langkah-langkah yang dilakukan dalam penelitian SLR ini adalah: 1) menentukan research question (RQ), 2) proses pencarian, 3) menentukan kriteria inclusion dan exclusion, 4) melakukan quality asessment, 5) melakukan data collecting, dan 6) melakukan analisa (Khairunnisa et al, 2022). Gambar 1 memperlihatkan proses langkah langkah yang dilakukan dalam penelitian ini.…”
Section: Metodeunclassified